A Critical Analysis of Chieftainship Democracy in Botswana - Chimbindi, Takawira (Advances in Social Sciences Research Journal, 2023)
This paper seeks to provide a critical study and understanding of the concept of Chieftainship (bogosi) as it relates to the embracement of democracy in Botswana. It shows how bogosi has maintained its strategic position, administrative power and influence amongst attempts by the colonial and postcolonial states to undermine it. It maintains that bogosi has been able to adjust to changing socio-economic and political landscapes in Botswana. While the institution’s powers have been slowly weakened by the government since independence. Chiefs and traditional institutions have used their legitimacy to strengthen their pliability. One can claim that chieftainship has been overtaken by events, it’s outdated, the reality is that the institution in Botswana has become central to government and cannot be cast-off. It is a traditional institution that plays a vital role in Botswana’s socio-political and economic system. The blending of the traditional Kgotla system and the modern democracy gives a dichotomy of dualism of tribal- government on the one hand and a western styled central government on the other yet well connected and balanced for bringing development to Batswana. This paper is not empirically grounded, and its content is a result of desktop and content analysis of literature from articles of authors that talked about Botswana chieftainship system. The paper hopes to trigger and provoke further deliberations and empirical studies on the contribution of Kgotla political system to transformation of democracy in Botswana.